Impact of climate change on the ecology of the Kyambangunguru crater marsh in southwestern Tanzania during the Late Holocene. (15th September 2018) - Coffinet, Sarah; Huguet, Arnaud; Bergonzini, Laurent; Pedentchouk, Nikolai; Williamson, David; Anquetil, Christelle; Gałka, Mariusz; Kołaczek, Piotr; Karpińska-Kołaczek, Monika; Majule, Amos; Laggoun-Défarge, Fatima; Wagner, Thomas; et al.
Abstract: Instrumental records of temperature and hydrological regimes in East Africa evidence frequent droughts with dramatic effects on population and ecosystems. Sources of these climatic variations remain largely unconstrained, partly because of a paucity of Late Holocene records. Here, we present a multi-proxy analysis of a 4-m continuous sediment core collected in the Kyambangunguru crater marsh, in southwest Tanzania, covering the last 4000 yrs (cal. BP). We used microscopic (macro-remains, microfossils, palynofacies, pollen), elemental (carbon, nitrogen contents), molecular (br GDGTs, n- alkanes) and compound-specific isotopic (δ 2 H n -alkanes) investigations to reconstruct the environmental history of the marsh. The multi proxy record reveals that, 2500 years ago, the marsh underwent a major ecological transition from a lake to a peatland. Temperature and hydrological reconstructions evidence warmer and drier conditions between 2200 and 860 cal. BP, which probably triggered the establishment of a perennial peatland. This study is one of the first combined temperature and precipitation record of Late Holocene in the region and highlights changes in the spatial distribution of the East African climate regimes. Several cold periods are observed, between 3300 and 2000 cal. BP and since 630 cal. BP, the latter corresponding to the Little Ice Age. Moreover, wetter conditions are reported during the Medieval Climate Anomaly in contrast to other north-eastern African records suggesting that Tanzania is located at the transition between two hydro-climatic zones (north-eastern versus southern Africa) and has experienced variable contributions of these two zones over the last millennium. Highlights: 4000-year continuous peat record of the Late Holocene in East Africa (SW Tanzania). Multi proxy approach evidences major ecological changes at ca. 2500 yr cal. BP. Detailed temperature and hydrology records highlight several cold events. More recent climate conditions seem connected to South African climate variability.